Impact of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers on the Inflammatory Response and Viral Clearance in COVID-19 Patients - Huang, Linna; Chen, Ziying; Ni, Lan; Chen, Lei; Zhou, Changzhi; Gao, Chang; Wu, Xiaojing; Hua, Lin; Huang, Xu; Cui, Xiaoyang; Tian, Ye; Zhang, Zeyu; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To evaluate the impact of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) on the inflammatory response and viral clearance in coronavirus disease 2019 (COVID-19) patients. Methods: We included 229 patients with confirmed COVID-19 in a multicenter, retrospective cohort study. Propensity score matching at a ratio of 1:3 was introduced to eliminate potential confounders. Patients were assigned to the ACEI/ARB group (n=38) or control group (n=114) according to whether they were current users of medication. Results: Compared to the control group, patients in the ACEI/ARB group had lower levels of plasma IL-1β [(6.20±0.38) vs. (9.30±0.31) pg/ml, P=0.020], IL-6 [(31.86±4.07) vs. (48.47±3.11) pg/ml, P=0.041], IL-8 [(34.66±1.90) vs. (47.93±1.21) pg/ml, P=0.027] and TNF-α [(6.11±0.88) vs. (12.73±0.26) pg/ml, P<0.01]. Current users of ACEIs/ARBs seemed to have a higher rate of vasoconstrictive agents (20% vs. 6%, P<0.01) than the control group. Decreased lymphocyte counts [(0.76±0.31) vs. (1.01±0.45)*10^9/L, P=0.027] and elevated plasma levels of IL-10 [(9.91±0.42) vs. (5.26±0.21) pg/ml, P=0.012] were also important discoveries in the ACEI/ARB group. Patients in the ACEI/ARB group had a prolonged duration of viral shedding [(24±5) vs. (18±5) days, P=0.034] and increased length of hospitalization [(24±11) vs. (15±7) days, P<0.01]. These trends were similar in patients with hypertension. Conclusions: Our findings did not provide evidence for a significant association between ACEI/ARB treatment and COVID-19 mortality. ACEIs/ARBs might decrease proinflammatory cytokines, but antiviral treatment should be enforced, and hemodynamics should be monitored closely. Since the limited influence on the ACEI/ARB treatment, they should not be withdrawn if there was no formal contraindication.